Comparison of Different Methods in Monthly Surface Runoff Estimation Based on the Monthly Curve Number - Zahra Parisay; Vahedberdi Sheikh; Abdolreza Bahreman; Komaki ChooghiBairam; Khodayar Abdollahi (پژوهش‌های آبخیزداری, 2019)
It is a matter of utmost importance to estimate accurately watersheds’ surface runoff in order to manage a region's water resources. Due to the inadequacy and lack of surface runoff monitoring in some watersheds, as well as high error and relatively high data demand of the daily runoff estimation methods, it is necessary to rely on the monthly runoff estimation methods. Different scenarios of combining monthly surface runoff estimation methods (the monthly SCS method, SCS-based runoff coefficient, the integrated curve number (CN), and the runoff coefficient method) with three methods of calculating monthly curve number (based on the leaf area index, on the retention potential, and on the average CN-based reference tables) as input parameters for the surface runoff estimation methods. These estimations were applied and compared across the Araz-Kouseh Watershed, east of the Province of Golestan. Results indicated that the monthly SCS method in combination with all methods of monthly CN has appropriately simulated the surface runoff with the Nash-Sutcliffe (NS) coefficient and bias values of higher than 0.6 and lower than 0.3, respectively. While the SCS-based runoff coefficient method performed poorly (with negative NS values and bias values above 4), particularly in combination with the average CN estimation based on the reference table. The integrated method of curve number and runoff coefficient in combination with all methods of monthly CN estimation indicated relatively acceptable results (with the NS values of about 0.6) during the calibration period; however, for the validation period, the results in combination with some monthly CN calculation methods were less reliable. Therefore, the monthly SCS method was selected as a suitable and robust method for the monthly surface runoff simulation of the Araz-Kouseh Watershed; thus it may be recommended for estimation of the water balance in similar watersheds in the region.